Translating social policy ideas: The Beveridge report, transnational diffusion, and post‐war welfare state development in Canada, Denmark, and France. (11th August 2021) - Béland, Daniel; Marchildon, Gregory P.; Mioni, Michele; Petersen, Klaus
Abstract: In the history of social policy in advanced industrial societies, the 1942 Beveridge Report stands as one of the most influential government‐sponsored reports ever published. In this article, we explore how the principles and the policy proposals formulated in the report diffused to other countries and how domestic actors adapted them to their local context through policy translation processes. The social policy ideas that Beveridge put forward in his 1942 report influenced post‐war policy debates in ways that varied greatly from country to country. To illustrate this claim, we analyse the reception and policy impact of this report over time in three different welfare states: Canada, Denmark, and France. This comparison shows how Beveridge's ideas influenced policy debates in different countries through translation processes that adapted these ideas to each country's institutional and political context.